IMPLEMENTASI PEMENUHAN HAK ATAS INFORMASI DAN PARTISIPASI MASYARAKAT DALAM PELAYANAN PENGUSULAN DATA TERPADU KESEJAHTERAAN SOSIAL (DTKS) DI KANTOR KELURAHAN OESAPA - Tomy Jeferson Katipana; Dara Pustika Sukma (Bajang Institute, 2025)
High-quality public service at the village level is a crucial foundation for good governance, particularly regarding community access to social welfare programs. The Integrated Social Welfare Data (DTKS) plays a vital role as the basis for determining social assistance recipients, thus the implementation of services related to proposing and updating this data at the Oesapa Village Office must adhere to legal principles. This study aims to examine and juridically analyze how the DTKS (Integrated Social Welfare Data) submission service is conducted at the Oesapa Village Office, reviewed from the perspective of the rights and obligations inherent to both the community as service users and village officials as service providers. Employing a juridical analysis approach, this research examines relevant legal norms from the Public Service Law, regulations concerning DTKS, as well as government administration regulations, and investigates their implementation through a study at the Oesapa Village Office. The analysis focuses on legal aspects related to fulfilling the basic rights of the community in the DTKS submission process (such as the right to accurate information, the right to be registered if eligible) and the compliance of officials in carrying out procedural and ethical service obligations. The research findings are expected to identify the alignment between regulations and practices in the field, uncover potential legal issues in implementation, and formulate juridical implications for improving the accountability and effectiveness of DTKS services at the village level to ensure citizens' rights are guaranteed